Simultaneous determination of noble metals, Sb and Hg by magnetic solid phase extraction on line ICP OES based on a new functionalized magnetic graphene oxide - García-Mesa, Juan Carlos; Montoro-Leal, Pablo; López-Guerrero, María del Mar; Vereda-Alonso, Elisa Isabel (Elsevier, 2019)
The aim of this study is to evaluate the extraction capacity of a new functionalized magnetic graphene oxide (MGO) to be employed in the automatic simultaneous preconcentration-determination of a relatively large number of elements with different properties by inductively coupled plasma optical emission spectrometry (ICP OES). A multimode sample introduction system (MSIS) cyclonic spray chamber was employed to generate and introduce vapours of Ag, Au, Ir, Os, Pd, Pt, Sb and Hg in the ICP torch. Several flow and chemical variables were optimized by two multivariate central composite designs. Detection limits between 0.05 μg L−1 for Hg, and 2.6 μg L−1 for Pd, and enrichment factors between 3 for Hg, and 33 for Os were obtained with a precision ≤5% (%RSD). The accuracy of the method was validated by determining the eight target elements in a certified reference material TMDA 54.5 and by the analysis of spiked tap water, mineral water and sea water samples taken from Málaga (Spain). The obtained results were in good agreement with the certified values and high recoveries were achieved for the spiked samples. Thus, the new adsorbent has demonstrated to be useful for the preconcentration of elements with quite different properties, such as noble metals, Sb and Hg, with a sample throughput of about 13 h−1 and low consumption of reagents and samples.
Keywords: Metales preciosos; ICP-OES; Magnetic solid phase extraction; Magnetic graphene oxide; PGMs; Antimony; Mercury